International financial centers as the «heart» of the global financial market - Шуба, Марина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
The article studies factors and conditions that contribute to the emergence of international financial centres. The role of international financial centers in the development of global financial market are considered, trends in their development are identified. The most famous international rankings of the world financial centers are analyzed.